A STUDY OF THE TEACHING-LEARNING SITUATION IN SOME SOUTHERN NIGERIA SCHOOLS OF AGRICULTURE - JIBOWO , A. A; ADEDOYIN, S. F. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2020)
The study objective was to analyse the dynamics of the teaching-learning situation in Southern Nigeria Agricultural Schools. Data were collected from 107 Agricultural Assistants-in-training and 54 Agricultural Superintendents-in-training, in January to March. 1981 through the questionnaire. Most respondents were males with a neutral attitude towards agriculture, although. they perceived their courses as relevant to their training lecture and demonstration were the commonly experienced teaching methods, practical classes were infrequent. Intensified practical classes use of more teaching methods and training more females in specific urban oriented fields such as poultry keeping, should improve the impact of the training schemes.